Characteristics of the environmental microscale and walking and bicycling for transportation among adults in Curitiba, Paraná State, Brazil - Adalberto Aparecido dos Santos Lopes; Marilson Kienteka; Rogério César Fermino; Rodrigo Siqueira Reis (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
The aim of this study was to analyze the association between the characteristics of the built and social and environmental microscale and walking and bicycling for transportation in adults in Curitiba, Paraná State, Brazil. A cross-sectional study was performed in 2009 with a household survey that included 1,419 adults. Objective evaluation of environment was performed on the resident's street segments, using an instrument for systematic observation consisting of six dimensions: "land use", "public transportation", "streetscape", "conditions and aesthetics", "places for walking and bicycling", and "social environment". The score for each dimension was obtained as the sum of positive items related to physical activity. The items for "public transportation" (≥ 1 items) and "places for walking and bicycling on the streets" (≥ 3 items) were dichotomized, while the scores for the other items were classified in tertiles. Walking and bicycling for transportation were assessed with the International Physical Activity Questionnaire (IPAQ). The data were analyzed using multilevel Poisson regression. Medium "streetscape" score was inversely associated with walking ≥ 150min/week (PR = 0.60; 95%CI: 0.40-0.91; VPC = 12%) and bicycling (PR = 0.54; 95%CI: 0.29-0.99; VPC = 60%). In conclusion, only "streetscape" was associated with walking and bicycling for transportation in adults.